Uphill performance: with poles, or not with poles, this is the question - Savoldelli, A.; Fait, A.; Callovini, A.; Stella, F.; Fornasiero, A.; Bortolan, L. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Introduction: During the last three decades there was a widespread use of poles during walking especially thanks to two different schools/techniques: Nordic Walking and Exerstriding. The use of poles seems to be beneficial for increasing fitness level due to the increase in energy cost and in total energy expenditure when compared with conventional walking (Figard-Fabre et al., 2010). Despite having a reduced energy cost (i.e. increased economy) is a recognized determinant of endurance performance (Bassett & Howley, 2000), the use of poles is also typical during trekking and vertical performances. Accordingly, it seems that people may decide to sacrify their walking/running economy in order to improve/ameliorate their ultra-marathon performances (Millet et al., 2012). Interestingly, when we analyse the scientific literature, we can point out that using poles in uphill is not such detrimental such using them in flat conditions (Perrey & Fabre, 2008). Recently, Giovanelli and colleagues (Giovanelli et al. 2019) investigated the effects of using poles on steep uphills, showing that walking with poles on steep inclines is slightly more economical than walking during sub-maximal exercise. Less is known about the effects of using poles on maximal exercise capacity (i.e. maximal oxygen uptake (VO2max)) and maximal uphill performance (e.g. vertical speed). The aim of this work was to investigate the effects of using poles at different speeds (from submaximal to maximal) on energy cost, rate of perceived exertion (RPE), oxygen uptake and performance. We either aimed to investigate the effects of speed on the force applied through the poles. Methods: Nine trained athletes (Performance Level 3 according to De Pauw et al., 2013), aged 25 to 45 years old, completed two GXT at a constant slope (25%), one with and one without poles, in a randomized order. We planned a 0.7 km/h increase of speed among the steps. Subjects performed five submaximal steps of four minutes duration (from 2.5 to 5.3 km/h), followed by subsequent steps of one-minute duration till volitional exhaustion. Subjects were asked to walk during the submaximal steps of the protocol. Results: The use of poles allowed the subjects to reach a higher VO2max (63.3 mlO2/kg*min and 60.3 mlO2/kg*min, with and without poles, respectively; +4.7%, p=0.022, d = 0.43, small) and a higher ascensional speed (1798 m/h and 1727 m/h, with and without poles, respectively; +4.0%, p=0.004, d = 0.29, small) at maximal exertion. During sub-maximal intensities energy cost was not affected using poles, but RPE at some speeds was lower when using poles. Poles frequency and the mean force applied through the poles increase with the increase of speed. Conclusion: The use of poles seems to be beneficial not only for fitness purposes but also for submaximal and maximal uphill performances. The use of poles seems to enhance maximal performance and reduce RPE at submaximal intensities without affecting energy cost that is partially in line with Perrey and Fabre (2008) and with Giovanelli and colleagues (Giovanelli et al., 2019). Further research is needed to verify the present results in outdoor settings.